Numerical chromosomal aberrations in Hodgkin's disease detected by in situ hybridisation on routine paraffin sections. Issue 7 (July 1997) - Pringle, J H; Shaw, J A; Gillies, A; Lauder, I
Abstract : AIMS: To visualise directly numerical chromosomal aberrations and polyploidy in both Hodgkin and Reed Sternberg (HRS) cells and background cells from cases of Hodgkin's disease using in situ hybridisation. METHODS: Non-isotopic DNA in situ hybridisation was applied to interphase cell nuclei of Hodgkin's disease within routine paraffin embedded tissue sections. Two a satellite DNA probes, specific for chromosomes 3 and 12, were used to evaluate the feasibility of this approach. Double labelling with immunocytochemical detection of the CD30 antigen was used to identify HRS cells. Cytogenetic normal diploid and triploid placental tissue served as controls. RESULTS: The eight cases of Hodgkin's disease investigated displayed frequent polysomy, while the majority of background cells showed disomy signals. CONCLUSIONS: Numerical chromosomal aberrations were detected in HRS cells from eight cases of Hodgkin's disease by in situ hybridisation. These data show that in Hodgkin's disease HRS cells frequently display polyploidy compared with background cells and are, therefore, probably the only neoplastic component in this disease. Correlations between polysomy and tumour type or grade could not be made from these data owing to the limited number of cases examined and to problems with interpreting data from truncated nuclei.